A Sociolinguistic Study of Code-Switching and Code-Mixing in Podcast mengANALISA: Identity Construction and Professional Positioning - Ida Aisyah Febiana; Diyah Atiek Mustikawati; Elok Putri Nimasari (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2026)
Nowadays, podcasts have emerged as popular digital communication platforms, particularly among younger audiences in Indonesia. The increasing use of bilingual expressions in podcasts reflects the growing interaction between local and global linguistic practices in digital media. This study investigated the forms, functions, and sociolinguistic meanings of code-switching and code-mixing in the Indonesian podcast MengANALISA hosted by Analisa Widyaningrum. Using a descriptive qualitative approach, the study applied the frameworks proposed by Shana Poplack and Pieter Muysken to classify bilingual utterances. The data were collected from the episode entitled “COACH or MENTOR: Which is More Important?” through documentation and verbatim transcription. The findings revealed 140 instances of code-mixing and 90 instances of code-switching, with insertion and intra-sentential switching emerging as the dominant forms. The bilingual expressions identified in the podcast served referential, expressive, directive, and phatic functions, particularly in discussions related to leadership, coaching, and self-development. Furthermore, the use of English within Indonesian discourse reflects broader sociolinguistic processes associated with professionalism, digital identity, and audience engagement. The findings contribute to contemporary sociolinguistic discussions by demonstrating that code-switching and code-mixing in digital podcast discourse function not only as linguistic structures but also as socially meaningful practices shaped by identity performance and communicative context.